Integrated halal assurance ecosystem (IHAE): The first step to integrate halal industry’s supply chain with smart halal contract agreement (SHCA) - Mahashofia, Dinnaya; Kusumawati, Frisca; Negara, Lingghia Putri Atma (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Indonesia plays a pivotal role in the global halal industry, yet its certification system remains largely administrative and inspection-based, creating gaps in compliance, traceability, and export readiness. This study proposes the Integrated Halal Assurance Ecosystem (IHAE) as a process- and technology-driven framework to ensure continuous halal integrity and enhance global competitiveness. Unlike existing models in Malaysia, the UAE, and Thailand that apply sectoral solutions, IHAE offers an integrated approach across the entire supply chain. Methods: Using a qualitative descriptive method combined with Problem Tree Analysis, SWOT, and PESTLE, this study identifies three key weaknesses in Indonesia’s halal system: the perception of certification as mere administration, the lack of real-time audit and supply chain integration, and the absence of an export readiness framework for halal micro, small, and medium enterprises (MSMEs). Findings: Findings highlight five strategic innovations: Halal Assurance Protocol (HAP), Halal Assurance Network (HAN), Smart Halal Contract Agreement (SHCA), Real-Time Halal Audit Trail System (RT-HATS), and Halal Export Readiness Rating System (HERRS). Conclusion: The proposed framework strengthens compliance, builds transparency, and supports MSME participation in global halal trade. Novelty/Originality of this article: The novelty of this article lies in presenting a comprehensive, technology-enabled assurance ecosystem that shifts Indonesia’s halal system from static certification toward dynamic, integrated, and globally competitive halal governance.